2022
DOI: 10.3390/ijms23031246
|View full text |Cite
|
Sign up to set email alerts
|

Janus Kinase Inhibitors Improve Disease Activity and Patient-Reported Outcomes in Rheumatoid Arthritis: A Systematic Review and Meta-Analysis of 24,135 Patients

Abstract: Pain, fatigue, and physical activity are major determinants of life quality in rheumatoid arthritis (RA). Janus kinase (JAK) inhibitors have emerged as effective medications in RA and have been reported to exert direct analgesic effect in addition to reducing joint inflammation. This analysis aims to give an extensive summary of JAK inhibitors especially focusing on pain and patient reported outcomes (PRO). MEDLINE, CENTRAL, Embase, Scopus, and Web of Science databases were searched on the 26 October 2020, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 116 publications
1
14
0
1
Order By: Relevance
“…In the MTX-IR population in which baricitinib and adalimumab were compared, the reduction in pain and disease activity observed with baricitinib was significantly greater than with adalimumab. These findings are consistent with a meta-analysis assessing a range of outcomes for JAK inhibitors versus placebo, MTX, or bDMARDs in RA, which demonstrated significant improvements in pain VAS and in measures of disease activity including CDAI, for JAK inhibitors versus placebo and in pain VAS and some measures of disease activity versus TNFi 17 . At some time points in the present study, greater improvement in fatigue was observed with baricitinib than with adalimumab; however, those differences were relatively limited.…”
Section: Discussionsupporting
confidence: 87%
“…In the MTX-IR population in which baricitinib and adalimumab were compared, the reduction in pain and disease activity observed with baricitinib was significantly greater than with adalimumab. These findings are consistent with a meta-analysis assessing a range of outcomes for JAK inhibitors versus placebo, MTX, or bDMARDs in RA, which demonstrated significant improvements in pain VAS and in measures of disease activity including CDAI, for JAK inhibitors versus placebo and in pain VAS and some measures of disease activity versus TNFi 17 . At some time points in the present study, greater improvement in fatigue was observed with baricitinib than with adalimumab; however, those differences were relatively limited.…”
Section: Discussionsupporting
confidence: 87%
“…In our study, JAKi were associated with HAQ-DI normalization and pain VAS reduction compared with TNFi at 6 months after starting treatment. The effectiveness of JAKi on patient-oriented outcomes among RA patients are well-established [25], including the effectiveness on pain among RA patients with low levels of in ammation [26]. This might be due to the direct effect of JAKi on signals on pain sensitivity [27], or the rapid-acting nature of these agents, within 24 hours [24], one week [28], and two weeks [10], which may also contribute to the improvements in HAQ-DI in the early stages of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…A recent extensive meta-analysis, demonstrating that JAKi showed a significantly greater pain-relieving effect compared with biologic DMARDs (bDMARDs) supported these findings [28 ▪ ] In addition, the CRP values indicating the intensity of the inflammatory reaction were also lower in the JAK inhibitor group [28 ▪ ]. In addition, a post-hoc analysis of phase 3 trials of baricitinib found pain reduction was similar between opioid users and nonusers, which was not observed for adalimumab, suggesting opioids attenuate pain reduction effects [29].…”
Section: Dmard and Biological Considerationsmentioning
confidence: 95%